The first complete hand-rearing of two neonatal finless porpoises - Masahiko Kasamatsu; Kazuhiro Hasegawa; Ikuo Wakabayashi; Masami Furuta; Hiroki Inoue; Hidetomo Iwano (PLoS ONE, 2025)
Hand-rearing of marine mammals is an essential technique for the husbandry of orphans in captivity or the wild, especially endangered cetacean species. The purpose of the present study was to establish a method for successful hand-rearing and evaluate the nutritional state of neonatal finless porpoises. Two neonate finless porpoises maternally neglected at 5 days of age (Day 5) (neonate A, animal A) and Day 4 (neonate B, animal B) were hand reared. The amount of each tube feeding and daily number of nursings for animals A and B during the lactation period were gradually increased to 1,355 and 1,120 ml and 16 and 14 times, respectively. The mean daily caloric intake during the lactation period and average increase in body weight of animals A and B were 2,048 ± 207 and 2,206 ± 169 kcal and 65.4 and 66.9 g/day, respectively. Hypoproteinemia and hypertriglyceridemia were observed in the two neonates during the early stage of hand-rearing. The plasma concentrations of 24 free amino acids in the neonatal porpoises were significantly higher compared with adult porpoises. Plasma valine, leucine, and isoleucine levels in the neonates were dramatically higher than those in adults. Hyperlipoproteinemia, characterized by a higher percentage of very-low-density lipoprotein and the appearance of midband, was also observed in the two neonates, along with hypertriglyceridemia. A hand-rearing method for finless porpoises was successfully established in this research. Nutritional evaluation of serum protein, free amino acids, and lipid components is needed to improve the survivability of hand-reared neonatal porpoises. The hand-rearing method established in the present study is an essential technique for the husbandry of finless porpoises and can be applied to the conservation of other members of the porpoise family, including vaquita and Yangtze finless porpoises, which are the most endangered dolphins in the world.